Desenvolvimento e validação de metodologia analítica para avaliação de alisquireno em formulação farmacêutica - Sangoi, Micheli Wrasse (2010)
Aliskiren is the first representative of a new class of drugs, the low molecular weight renin inhibitors, orally active and clinically used in a new effective treatment for hypertension. In the present study, the methods were developed and validaded for assessment of aliskiren in pharmaceutical products. Aliskiren samples were also submitted to the physicochemical tests, meeting the specifications. The analysis by reversed-phase liquid chromatography were performed using Waters XBridge (150 mm x 4.6 mm i. d.), maintained at 25 °C. The mobile phase was consisted of acetonitrile/ water (95:5, v/v)/ 25 mM phosphoric acid pH 3.0 (40:60, v/v), run at flow rate of 1 mL/min and using UV detection at 229 nm. The chromatographic separation was obtained within 3.68 minutes. The spectrophotometric method was also developed and validaded, and the aliskiren can be quantified at 279 nm, using water as diluent. The procedures were validated evaluating parameters such as the specificity, linearity, precision, accuracy, limits of detection and quantitation, and robustness, giving results within the acceptable range. The proposed methods were applied for the analysis of pharmaceutical products, showing significant correlation (P > 0.05) of the results. The dissolution test was developed using 900 mL of 0.1 M of chloridric acid 37 ± 0.5 °C as dissolution medium, apparatus paddle at a stirring rate of 50 rpm and quantitation by spectrophotometric method. Therefore, the procedures can be applied to improve the quality control of pharmaceutical products and to assure the safety and therapeutic efficacy of the drug.